Cell‐Inspired All‐Aqueous Microfluidics: From Intracellular Liquid–Liquid Phase Separation toward Advanced Biomaterials. Issue 7 (11th February 2020) - Ma, Qingming; Song, Yang; Sun, Wentao; Cao, Jie; Yuan, Hao; Wang, Xinyu; Sun, Yong; Shum, Ho Cheung
Abstract: Living cells have evolved over billions of years to develop structural and functional complexity with numerous intracellular compartments that are formed due to liquid–liquid phase separation (LLPS). Discovery of the amazing and vital roles of cells in life has sparked tremendous efforts to investigate and replicate the intracellular LLPS. Among them, all‐aqueous emulsions are a minimalistic liquid model that recapitulates the structural and functional features of membraneless organelles and protocells. Here, an emerging all‐aqueous microfluidic technology derived from micrometer‐scaled manipulation of LLPS is presented; the technology enables the state‐of‐art design of advanced biomaterials with exquisite structural proficiency and diversified biological functions. Moreover, a variety of emerging biomedical applications, including encapsulation and delivery of bioactive gradients, fabrication of artificial membraneless organelles, as well as printing and assembly of predesigned cell patterns and living tissues, are inspired by their cellular counterparts. Finally, the challenges and perspectives for further advancing the cell‐inspired all‐aqueous microfluidics toward a more powerful and versatile platform are discussed, particularly regarding new opportunities in multidisciplinary fundamental research and biomedical applications. Abstract : Inspired by the liquid–liquid phase separation of membraneless organelles, all‐aqueous microfluidics exploit an aqueous two‐phase system to tailor the aqueous structures and shape the formation of materials. This approach is biocompatible for encapsulation, assembly, and patterning of biomolecules and cells in a near‐physiological environment, which enables the state‐of‐art design of advanced biomaterials with exquisite structural proficiency and diversified biological functions.